(untitled) - Huck, Virginia (New York, 1955)
"The 3M Story" is a history of a successful corporation, but it is more than that. It is a tribute to the people who made such success possible, the employees of 3M past and present, and its many stockholders. The tremendous growth of Minnesota Mining and Manufacturing Company is due to the ingenuity of these men and women, their faith, industriousness, and above all, their ability to work together down through the years.
Keywords: Minessota mining and manufacuring company